(9x-4)(x-1)=

Simple and best practice solution for (9x-4)(x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-4)(x-1)= equation:


Simplifying
(9x + -4)(x + -1) = 0

Reorder the terms:
(-4 + 9x)(x + -1) = 0

Reorder the terms:
(-4 + 9x)(-1 + x) = 0

Multiply (-4 + 9x) * (-1 + x)
(-4(-1 + x) + 9x * (-1 + x)) = 0
((-1 * -4 + x * -4) + 9x * (-1 + x)) = 0
((4 + -4x) + 9x * (-1 + x)) = 0
(4 + -4x + (-1 * 9x + x * 9x)) = 0
(4 + -4x + (-9x + 9x2)) = 0

Combine like terms: -4x + -9x = -13x
(4 + -13x + 9x2) = 0

Solving
4 + -13x + 9x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(4 + -9x)(1 + -1x) = 0

Subproblem 1

Set the factor '(4 + -9x)' equal to zero and attempt to solve: Simplifying 4 + -9x = 0 Solving 4 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -9x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -9x = 0 + -4 -9x = 0 + -4 Combine like terms: 0 + -4 = -4 -9x = -4 Divide each side by '-9'. x = 0.4444444444 Simplifying x = 0.4444444444

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {0.4444444444, 1}

See similar equations:

| 10x-1=5x+49 | | 6x-8=7-x | | 4(2m-3)=-44 | | 4x-6=10x+14 | | 19=-4(h+5)+h | | x+3-2x+5=10 | | 2x-2=5x-12 | | 4w^2=4w+3 | | 7x-3x=45-4x | | 35=(2x+3)*x | | 6x+5=4x-4 | | 2*1/3+2/1/3=x | | 4x-2x-2=2x | | -(8x-1)+x=-6x+6(x+6) | | x+2=-2x^2 | | 18x^3y-6x^7y=0 | | 2.3w-3.2+4.1=-6 | | 6x+14=29 | | 9t^2+2=9t | | 6x^2-21x-45=0 | | 7c^2-2c=1 | | 25x^3+5x^2-10x-2=0 | | m^2-14m+49=0 | | x^2+16x+53= | | -14=8-3a | | x^2+20x-18=0 | | -z^2+6=-5z | | m+2m+(m+10)=180 | | 7x^2-x-1=0 | | 4x-x+4=2x-6+14 | | .3k^2-6k=2.4 | | 1005=0.005x+0.95 |

Equations solver categories